Pluto's Antipodal Terrains Imply a Thick Subsurface Ocean and Hydrated Core - C. Adeene Denton; Brandon C. Johnson; Shigeru Wakita; Andrew M. Freed; H. Jay Melosh; S. Alan Stern (Geophysical Research Letters)
Abstract Recent analysis of New Horizons data revealed an ∼1,000‐km‐diameter region of large‐scale lineations antipodal to Sputnik Planitia, the 1,200 × 2,000 km elliptical impact basin on Pluto's anti‐Charon hemisphere. At the available resolution, these lineations are similar to antipodal terrains associated with large impact basins elsewhere in the Solar System. Here, we simulate the Sputnik Planitia‐forming impact and track stress waves through a Pluto‐like target body to the antipode. We find that the Sputnik Planitia‐forming impact is capable of producing significant antipodal terrains and the observed lineations may be extensional graben. The extent and mode of deformation at the antipode, however, is sensitive to ocean thickness and core composition. Simulations that best reproduce the observed terrains imply that Pluto may have hosted a >150‐km‐thick ocean and a hydrated core at the time of impact.